Educational outcome as a new dimension of quality assessment for private colleges : an exploratory perspective / Nooraini Mohamad Sheriff - Mohamad Sheriff, Nooraini (Institute of Quality and Knowledge Advancement (InQKA) and University Publication Centre (UPENA), 2007)
This study determined the commonly addressed quality dimensions for higher education and student's perceived importance of a new quality dimension that is educational outcome. Data were solicited from 808 newly enrolled students in 72 multi-disciplined private colleges in Malaysia via the Simple Random Sampling method. A two part questionnaire consisting of background data, student's perceived importance of private college's educational outcome were distributed through the drop-off method and mail survey. Likert-like scale with values ranging from 0 (Not applicable), 1 (low) to 7 (high) were used to obtain the said responses. The research uncovered that the Input and Process dimensions have often been emphasized as quality dimensions in higher education. However, student's too have perceived numerous elements of the Output dimension to be extremely important. They are acquiring adequate subject matter knowledge (59%), communication skills (51%) and analytical skills (48%). Hence implying the possible need to include the Output dimension as a new dimension of quality assessment for higher education. This findings signify the need for management of private colleges to pay serious attention to their educational outcome and the inputs as well as processes leading to them. Though intangible educational outcome be successfully utilized as their sustainable competitive advantage in battling the ferociously competitive private higher education market.